Ear-Specific Hemispheric Asymmetry in Unilateral Deafness Revealed by Auditory Cortical Activity - Han, Ji-Hye; Lee, Jihyun; Lee, Hyo-Jeong (Frontiers in Neuroscience, 2021)
Profound unilateral deafness reduces the ability to localize sounds achieved via binaural hearing. Furthermore, unilateral deafness promotes a substantial change in cortical processing to binaural stimulation, thereby leading to reorganization over the whole brain. Although distinct patterns in the hemispheric laterality depending on the side and duration of deafness have been suggested, the neurological mechanisms underlying the difference in relation to behavioral performance when detecting spatially varied cues remain unknown. To elucidate the mechanism, we compared N1/P2 auditory cortical activities and the pattern of hemispheric asymmetry of normal hearing, unilaterally deaf, and simulated acute unilateral hearing loss groups while passively listening to speech sounds delivered from different locations under open free field condition. The behavioral performances of the participants concerning sound localization were measured by detecting sound sources in the azimuth plane. The results reveal a delayed reaction time in the right-sided unilaterally deaf group for the sound localization task and prolonged P2 latency compared to the left-sided unilaterally deaf group. Moreover, the right-sided unilaterally deaf group showed adaptive cortical reorganization evidenced by increased responses in the hemisphere ipsilateral to the intact ear for individuals with better sound localization whereas left-sided unilateral deafness caused contralateral dominance in activity from the hearing ear. The brain dynamics of right-sided unilateral deafness indicate greater capability of adaptive change to compensate for impairment in spatial hearing. In addition, cortical N1 responses to spatially varied speech sounds in unilateral deaf people were inversely related to the duration of deafness in the area encompassing the right auditory cortex, indicating that early intervention would be needed to protect from maladaptation of the central auditory system following unilateral deafness.